1990
DOI: 10.1161/01.hyp.15.2_suppl.i157
|View full text |Cite
|
Sign up to set email alerts
|

Sodium intake modulates the development of cardiac hypertrophy in two-kidney, one clip rats.

Abstract: Sodium homeostasis exerts a powerful influence on the cardiovascular system in normotensive and hypertensive animals. Previous studies indicate that factors other than blood pressure can influence cardiac hypertrophy. In the present experiments, we evaluated the effects of different sodium diets in the two-kidney, one clip hypertension model in the rat. After the renal artery had been cupped, the rats received a normal sodium (177 meq/kg), high sodium (517 meq/kg), and low sodium (7 meq/kg) diet during 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Experimentally, dietary salt loading has been repeatedly demonstrated to increase and exaggerate ABP in multiple experimental models including Dahl salt-sensitive rats ( 22 , 38 ), deoxycorticosterone acetate-salt ( 23 , 25 ), chronic infusion of angiotensin II ( 28 ), and reduced renal mass ( 18 , 19 , 21 ). In regard to 2K1C models of renovascular hypertension, the majority of studies report that a high-NaCl diet does not exaggerate ABP ( 10 , 15 , 35 , 49 , 51 ). However, these previous studies largely relied on tail-cuff measurements of ABP or ABP measurements at a single time point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, dietary salt loading has been repeatedly demonstrated to increase and exaggerate ABP in multiple experimental models including Dahl salt-sensitive rats ( 22 , 38 ), deoxycorticosterone acetate-salt ( 23 , 25 ), chronic infusion of angiotensin II ( 28 ), and reduced renal mass ( 18 , 19 , 21 ). In regard to 2K1C models of renovascular hypertension, the majority of studies report that a high-NaCl diet does not exaggerate ABP ( 10 , 15 , 35 , 49 , 51 ). However, these previous studies largely relied on tail-cuff measurements of ABP or ABP measurements at a single time point.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the time of dietary salt manipulation may represent another important factor. Previous studies ( 10 , 15 , 35 , 49 , 51 ) administered salt diets either at the time of renal artery clipping or after the establishment of hypertension rather than acclimating animals to the respective diet to mimic chronic dietary salt consumption in clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that salt-sensitive hypertensive patients were more prone to develop myocardial hypertrophy and cardiovascular events (Chamarthi et al, 2010). Previous studies suggested that the potential mechanisms underlying high-salt-induced myocardial hypertrophy mainly included hemodynamic changes, sodium serum levels, increased sodium influx of cardiomyocytes, activation of cardiac renin-angiotensin-aldosterone system (RAAS) and activation of cardiac sympathetic nervous system (Gallo et al, 1990; Galderisi et al, 1991; Harmsen and Leenen, 1992; Le Corvoisier et al, 2010; He and Macgregor, 2012). However, the mechanism for high-salt-induced myocardial hypertrophy still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A dissociation between blood pressure and cardiac hypertrophy in 2K1C rats has been reported (Lindpaintner & Sen 1985;Gallo et al 1990). In their studies, sodium restriction resulted in reversal of cardiac hypertrophy but did not lower blood pressure.…”
Section: Discussionmentioning
confidence: 89%